Ultrasonic Study of Cyclohexane with o-Xylene at Different Temperatures - Narendra, K.; Srinivasu, Ch.; Narayana Murthy, P. (Asian Journal of Chemistry, 2010)
Molecular interactions have been studied in binary liquid mixtures of cyclohexane and o-xylener) and viscosity (h) measurements at 303.15, 308.15, 313.15b), intermolecular free length (Lf), free volume (Vm), internal pressure (p) were by ultrasonic velocity (u), density ( and 318.15 K and at different mole fractions. Acoustical parameters such as adiabatic compressibility ( calculated from the experi-mental data. The investigations on the binary mixture containing non-polar, non-polar liquids shows weak induced dipole-induced dipole attractions.